Indonesian Continuing Professional Development Implementation: Knowledge Development Aspect of Yogyakarta Senior Secondary School Mathematics Teachers - Theresia Veni Tri Nugraheni; Jailani Jailani (SEAMEO Regional Centre for QITEP in Mathematics, 2018)
Continuing Professional Development (CPD) contributes to teacher competencies, teaching practice quality, and student achievement. Based on a literature review, we found that there were three aspects of CPD. The CPD aspects that we found were: knowledge development; skill development; and knowledge dissemination. In this study, we focused on describing:(1) the CPD implementation, and (2) the barriers faced by senior secondary school mathematics teachers in Kulon Progo Regency in conducting the aspect of knowledge development. This type of study is descriptive research using a mixed method with convergent parallel design. The research subjects were all senior secondary school mathematics teachers in Kulon Progo Regency who participated in The Indonesian Teacher Competency (Uji Kompetensi Guru) in 2015 and 33 teachers were selected. Data werecollected through a questionnaire, documentation, and interviews, and analysed using descriptive techniques. The results showed that the CPD implementation in the aspect of knowledge development of senior secondary school mathematics teachers in Kulon Progo Regency was poor. The greatest barriers experienced by teachers related to conducting the aspect of knowledge development were an overwhelming workload, lack of selfmotivation, and inadequate place and time. Based on these findings, we suggested that teachers needed to be helped to develop their understanding and awareness of how CPD can improve their competencies, teaching practice quality, and student achievement. We also suggested that the government and stakeholders should encourage and facilitate teachers to participate actively to CPD activities that reach out teachers’ need.